The Effectiveness Analysis of Discovery Learning Assisted by Interactive Video toward Social Study Critical Thinking Skills of Primary School (Universitas Negeri Semarang, 2020)
Critical thinking skills must be owned by primary school students to face the 21st-century learning era. It can be trained in schools by implementing a discovery learning model in learning processes. This research aims to analyze and find out how discovery learning effectiveness assisted by interactive video toward critical thinking skills of Social study for fourth graders. The research methodology was quasi-experimental research while the technique of sampling was purposive sampling. In this research, Public Primary School 02 Pringapus functions as control group which was intervened by discovery learning and Public Primary School 01 Pringapus functions as experimental group which was intervened by discovery learning assisted by interactive video. The techniques of collecting data were critical thinking skill question, questionnaire, interview, and documentation. The results of classical accomplishment showed that the result of control group was 54.84% with average score 70. Meanwhile, the experimental group obtained 96.67%, with average score 76.67. The results of n-gain score of control group was 0.34 while the experimental group was 0.42. Both of them were categorizeed moderate. The findings showed that discovery learning implementation assisted by interactive video was effective in improving social study critical thinking skills of primary school students. This research is expected to be basis of developing and improving social study critical thinking skills for primary school students.